Nepal’s agrifood system structure and drivers of transformation - Xinshen Diao; Ellis, Mia; Fang, Peixun; Pauw, Karl; Pradesha, Angga; Thurlow, James (International Food Policy Research Institute, 2023)
Nepal experienced annual economic growth of 5.0 percent between 2009 and 2019 (World Bank 2023b). Thanks to a relatively slow population growth rate of 1.4 percent, the living standards of most Nepalis improved during this period; this allowed Nepal to graduate in 2019 from a low-income country to a lower-middle-income country. Nepal’s economy, however, was severely affected by the COVID-19 pandemic, with GDP declining by 2.4 percent in 2020 and growing only modestly in 2021. Fortunately, the country was largely spared the adverse effects of global commodity market disruptions arising from the Russia-Ukraine war that started in 2022 and from the 2023 global recession (Arndt et al. 2023; Diao and Thurlow 2023). Nepal’s GDP growth is now projected to reach 5.1 percent in 2023 and 4.9 percent in 2024 (World Bank 2023a); this suggests that the economy is resuming its pre-pandemic growth trajectory. Agriculture remains an important sector, accounting for 25 percent of Nepal’s GDP and 30 percent of its jobs. In this brief, we further unpack Nepal’s historical and projected economic growth trajectory in order to better understand the role of agriculture, and of the broader agrifood system (AFS), in the performance and transformation of its economy.